(untitled) (American Journal of Economics and Business Innovation, 2024)
Organizational performance is a cornerstone of any thriving institution, serving as a critical measure of how effectively an organization meets its goals and fulfills its mission. Higher performance which is the desire of many organizations is characterized by their strategic vision, cohesive culture, and resilient processes, which collectively drive sustainable success. Non-achievement of organizational goals by textile firms can manifest as a result of discrepancies between the organization’s strategic objectives and the supply chain’s operational goals. The research therefore sought to assess the role supply chain management practices on organizational performance, moderated by the competitive edge of textile firms in Kenya. The study specifically sought to determine the effect of green procurement, reverse logistics, and outsourcing on organizational performance moderated by competitive edge. The study was guided by Just in Time Theory, Theory of Constraints, and the Resource Based View Theory. Explanatory research design was used and a sample of 216 heads of logistics and procurement departments was used, for a total of 52 textile firms in Kenya. The findings showed that green procurement (β1=0.282, p<0.05), reverse logistics (β2=0.287, p<0.05) and outsourcing (β3=0.331, p<0.05) had a positive and significant effect on organizational performance. Competitive edge enhances the relationship between green procurement (β=-0.069; p<0.05), reverse logistics (β=-0.137; p<0.05), outsourcing (β=-0.122; p<0.05) and organizational performance. Boosting competitive edge makes the supply chain efforts more effective in improving firm performance. Organizations should leverage on competitive edge to enhance the impacts of green procurement, reverse logistics, and outsourcing on performance.